Evaluasi Penggunaan Tepung Daun Pisang pada Periode Starter untuk Mendapatkan Pertumbuhan Kompensasi Ayam Broiler - D M Suci; L Rosaline; R Mutia (Media Peternakan, 2005)
The purpose of this experiment was to study the effect of banana leaf meal in diet (0-3 weeks) on compensatory growth of broiler (3-5 weeks). One hundred and twenty day old chick were fed one of three different treatment : P1 used 0 % banana leaf meal from 0-5 weeks (R1), P2 used 5 % banana leaf meal (R2) from 0-3 weeks and R1diet from 3-5 weeks and P3 used 10 % banana leaf meal (R3) from 0-3 weeks and R1 diet from 3-5 weeks. Each of experiment diets contained of 2900 kcal/kg metabolizable energy and 21% crude protein. Completely Randomized Design was used in this experiment. The results showed that feeding with banana leaf meal at 0-3 weeks significantly (P < 0.01) reduced feed intake, and body weight gain (P < 0.05). Recovery periods (3-5 weeks) did not show the compensatory growth because of significantly reduced (P < 0.05) feed intake and body weight gain. Conclusion showed that effect of banana leaf meal in diet (0-3 weeks) on compensatory growth of broiler (3-5 weeks) could not maximize final body weight. Key words: banana leaf meal, compensatory growth, broiler